2008
DOI: 10.1007/s12223-008-0055-5
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex PCR detection of the antibiotic resistance genes in Staphylococcus aureus strains isolated from auricular infections

Abstract: Thirty-five Staphylococcus aureus strains from auricular infections were isolated. The identification of strains was confirmed by Api ID 32 Staph strips, the antibiotic susceptibility test was performed using ATB Staph kit. PCR assay was used to detect the oxacillin resistance gene (mecA) and the erythromycin genes (ermA, ermB, ermC, msrA and mef). The susceptibility profile of all strains revealed a low resistance level to oxacillin and erythromycin. The PCR results show that 60 % of the strains are mecA posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 26 publications
8
28
0
Order By: Relevance
“…Also, this study found that efflux genes such as msrA gene was present either alone or in association with other genes (23.7%), while the mefA gene was absent from all tested isolates. These results concur with those described by Zmantar et al [35], who reported the same observation. Furthermore, we found a predominance of ermC gene (27/38) among MLS resistance genes.…”
supporting
confidence: 94%
“…Also, this study found that efflux genes such as msrA gene was present either alone or in association with other genes (23.7%), while the mefA gene was absent from all tested isolates. These results concur with those described by Zmantar et al [35], who reported the same observation. Furthermore, we found a predominance of ermC gene (27/38) among MLS resistance genes.…”
supporting
confidence: 94%
“…In comparison with other studies such as the ones mentioned for each gene in the description above, the current results show that the mentioned genes are identified approximately in a similar number as can be found in literature (Harbarth et al, 2006;Zmantar et al, 2008;Crăciunaş et al, 2010).…”
Section: Resultssupporting
confidence: 87%
“…Even more, the genes mentioned were investigated on isolates from blood and urine specimens in Turkey (Aktas et al, 2007) or from unknown MRSA carriers (Harbarth et al, 2006). Other examples are presented as Crăciunaş et al (2010) investigated mecA, femA, ermA, ermB, ermC on clinical isolates, and Zmantar et al (2008) used for their investigation Staphylococcus aureus strains isolated from auricular infections.…”
Section: Introductionmentioning
confidence: 99%
“…The possible reasons for this type of discrepancy are that the isolates appeared to show poor expression of mecA genes or production of methicillinase (alteration of PBP subtypes) or seem to overproducing β-lactamase. The phenotypic expression of resistance could vary due to growth conditions which are also involved in the expression of methicillin resistance (Zmantar et al, 2008;Turutoglu et al, 2009 andTurkylmaz et al, 2010).…”
Section: Genotypic Identification Of Mrsa Isolatesmentioning
confidence: 99%